Study of the three‐phase saturated transformer coupling new bridge‐type SSFCL. (11th December 2012) - Mo, Yujie; Jiang, Daozhuo; Wu, Zhaolin
SUMMARY In this paper, the principles of the three‐phase saturated transformer coupling new‐type solid state fault current limiter (SSFCL) are studied using the equivalent circuit method; in addition, considering the nonlinearity of the iron core material in the saturated transformer, the circuit field‐coupled 3‐D finite‐element analysis is employed to investigate the transient performance of the proposed SSFCL. The analysis and simulation results show that the novel SSFCL has negligible impact on the power system during the normal operating stage, automatic response to the short‐circuit fault, and especially low secondary voltage level during the current‐limiting stage, which are of great significance to the reduction of the thyristor voltage level, the DC reactance, as well as the volume and cost of the whole SSFCL. The current‐limiting effect is also tested in the simulation of a multi‐machine power system with the protection of SSFCL. Last, the comparison of the simulation and experimental results proves the feasibility of the proposed SSFCL. Copyright © 2012 John Wiley & Sons, Ltd.